First record of the genus Bradybatus Germar (Coleoptera, Curculionidae, Anthonomini) from China with description of a new species - Li, Yizhe; Lü, Heyu; Jiang, Chunyan; Zhang, Runzhi (Zootaxa, 2024)
The genus Bradybatus Germar, 1823 is reported from China for the first time. A new species is described and illustrated under the name Bradybatus (Bradybatus) keerqinensis Lü and Zhang sp. n. from Inner Mongolia Autonomous Region, China. This new species can be easily distinguished from other species of Bradybatus by the large body size, black color, pronotum length/width ratio about 1.21–1.27 without longitudinal stripe, elytra length/width ratio about 1.85–2.00 without oblique or transverse band, and pedon uniformly curved C-shaped (in lateral view), sides subparallel (in dorsal view), with distinctly narrow apex. An identification key to all known species of the subgenus Bradybatus is updated. The biological characteristics of the species are also provided.